Information system for plant-insect interactions in four subcatchments of Mt. Isarog Natural Park - Carpio, Avegail D. (Animo Repository, 2012)
Mount Isarog Natural Park(MINP) which is 10,112 hectares wide has an abounding diversity of fauna and flora. The information that can be extracted from the natural resources in Mt. Isarog starting with the species behavior and interdependence, to profiling its gene sequences and determining plant compound content, globally renews the present Biology These data must be converted into knowledge leading to a discovery of novel products and facts about the ecosystem that would benefit humans ad the ecosystem itself.The Mt. Isarog's Flora and Associated Anthropods' Basic, Genomic and Spectroscopic Profile Biological Behavior and Interdependence: An Information System (MIFAABGSBBI) basically documents the information obtained from MINP's flora and associated anthropods through an efficient database management system encapsulated in an effectual web-based information system. Presently there is no online information system about Mt. Isarog species particularly flora and associated anthropods that records and provides detailed information about their biological features and behaviors. The information system will serve as an avenue for advanced researches about species interdependence, for food web diagrams are generated. Upon discovering and exceptional trait of species which depends on another particular species, their genomic and spectroscopic profile can be analyzed for comparative analysis.